2017
DOI: 10.1002/eji.201746959
|View full text |Cite
|
Sign up to set email alerts
|

Post‐translational regulation of antiviral innate signaling

Abstract: The innate immune system initiates immune responses by pattern-recognition receptors (PRR). Virus-derived nucleic acids are sensed by the retinoic acid-inducible gene I (RIG-I)-like receptor (RLR) family and the toll-like receptor (TLR) family as well as the DNA sensor cyclic GMP-AMP (cGAMP) synthase (cGAS). These receptors activate IRF3/7 and NF-κB signaling pathways to induce the expression of type I interferons (IFNs) and other cytokines firing antiviral responses within the cell. However, to achieve a favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 141 publications
(159 reference statements)
0
81
0
Order By: Relevance
“…and IFN production has been provided. 35 Type-I to -III IFNs are known to act as key effectors in the innate immune response against HBV infection. Moreover, IFN-α treatment is licensed for hepatitis B therapy and has resulted in virus clearance in some patients.…”
Section: Previous Evidence On the Relationship Between Nf-κb Activationmentioning
confidence: 99%
“…and IFN production has been provided. 35 Type-I to -III IFNs are known to act as key effectors in the innate immune response against HBV infection. Moreover, IFN-α treatment is licensed for hepatitis B therapy and has resulted in virus clearance in some patients.…”
Section: Previous Evidence On the Relationship Between Nf-κb Activationmentioning
confidence: 99%
“…However, a variety of non-histone proteins, both cytoplasmic and nuclear, are now known to be HDAC substrates (Seto & Yoshida, 2014). HDACs work in equilibrium with histone acetyl transferases to control the acetylation level of proteins and influence diverse biological processes such as gene expression (Sterner & Berger, 2000), protein trafficking (Li & Yang, 2015), and the innate immune response (Zhou, He, Wang, & Ge, 2017). Consequently, the imbalance in protein acetylation due to aberrant function of HDACs or histone acetyl transferases contributes to multiple human diseases such as cancer (Liu, Li, Wu, & Cho, 2017), neurodegeneration (Cook, Stankowski, Carlomagno, Stetler, & Petrucelli, 2014), and infection (Jeng, Ali, & Ott, 2015;Song & Walley, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another goal of nucleic acid packaging into a particle lies in the presentation of viral nucleic acids leading to the activation of specific immune receptors which induce the synthesis of type I interferons (INF) and other cytokines triggering the antivirus response [49]. It has been demonstrated that long DNA and RNA molecules may be incorporated into VLPs.…”
Section: Natural Sources For Vlp Bioengineering and The Specificmentioning
confidence: 99%
“…Posttranslational protein modifications and covalent bonds between the modifying molecules and the functional groups in the polypeptide chains are of great importance for immune homeostasis during the antiviral response. The balance between phosphorylation, ubiquitination, methylation, acetylation, SUMOylation, ADP-ribosylation, and glutamilation of a certain antigen performs the fine adjustment of the host's antiviral response [49,58]. The structural proteins for VLP production when synthesized in the eukaryotic expression systems undergo a number of posttranslational modifications.…”
Section: Natural Sources For Vlp Bioengineering and The Specificmentioning
confidence: 99%